Relapsing Into Crime Versus a Notion of Criminal Career in Polish Criminological Studies (Biuletyn Kryminologiczny, 2021)
The Criminology Department of the Institute of Law Studies of the Polish Academy of Sciences, has launched the study over criminal careers backgrounds and advances - of those who committed punishable acts of juvenile oﬀenders. It should be stressed that deﬁnitions of relapsing into crime, or of criminal career, are much wider than those of recidivism in the meaning of the Polish criminal law. In this endeavor, we took the “criminal career” deﬁnition as our starting point. Polish criminal law strictly deﬁnes “recidivism”, while legal scholars moreover deﬁne the “penitentiary recidivism” (the one consisting in serving more than one custodial sentence/s). The deﬁnitions of “criminal career”, as formulated by criminologists, are however much wider, and also rather diverse. Criminological theories that arise from the three basic paradigms – classical, positivistic, and anti-naturistic ones – are to diﬀerent degrees connected with the problems of relapsing into crime and repeated crime. In this paper we present some selected concepts to deﬁne the term “criminal career”, as well as the deﬁnition adopted by our research team to be used in further studies. Zespół badawczy Zakładu Kryminologii INP PAN od 2017 r. prowadzi badania dotyczące mechanizmów powstawania i rozwoju karier przestępczych osób popełniających uprzednio czyny karalne w okresie nieletniości. Warto podkreślić, że przyjmowane w kryminologii defnicje powrotności do przestępstwa, kariery kryminalnej czy kariery przestępczej, są znacznie szersze od defnicji recydywy w znaczeniu jurydycznym, którą operuje polskie prawo karne. Punktem wyjścia do naszych badań jest odpowiedź na pytanie o to, jak defniujemy pojęcie „kariera kryminalna”. Na gruncie polskiego prawa karnego formalnie zdefniowano pojęcie recydywy a w nauce prawa karnego zdefniowano także pojęcie recydywy penitencjarnej. Kryminologiczne defnicje pojęcia „kariery kryminalnej” są jednak znacznie szersze i dość zróżnicowane. Teorie kryminologiczne, wpisane w trzy podstawowe paradygmaty: klasyczny, pozytywistyczny i antynaturalistyczny, w różnym stopniu odwoływały się do problematyki powrotności do przestępstwa i przestępczości wielokrotnej.Artykuł ma na celu syntetyczne zestawienie wybranych koncepcji dotyczących defniowania pojęcia kariery kryminalnej oraz zaprezentowanie defnicji sformułowanej przez nasz zespół badawczy na potrzeby dalszych badań w tym zakresie.